Endovascular therapy outcome in isolated posterior cerebral artery occlusion strokes: A multicenter analysis of the Swiss Stroke Registry. (June 2023) - Maulucci, F; Disanto, G; Bianco, G; Pileggi, M; Fischer, U; Padlina, G; Strambo, D; Michel, P; Kahles, T; Nedeltchev, K; Fisch, U; Bonati, L; et al.
Purpose: There is little data on the safety and efficacy of endovascular treatment (EVT) in comparison with intravenous thrombolysis (IVT) in acute ischemic stroke due to isolated posterior cerebral artery occlusion (IPCAO). We aimed to investigate the functional and safety outcomes of stroke patients with acute IPCAO treated with EVT (with or without prior bridging IVT) compared to IVT alone. Methods: We did a multicenter retrospective analysis of data from the Swiss Stroke Registry. The primary endpoint was overall functional outcome at 3 months in patients undergoing EVT alone or as part of bridging, compared with IVT alone (shift analysis). Safety endpoints were mortality and symptomatic intracranial hemorrhage. EVT and IVT patients were matched 1:1 using propensity scores. Differences in outcomes were examined using ordinal and logistic regression models. Findings: Out of 17, 968 patients, 268 met the inclusion criteria and 136 were matched by propensity scores. The overall functional outcome at 3 months was comparable between the two groups (EVT vs IVT as reference category: OR = 1.42 for higher mRS, 95% CI = 0.78–2.57, p  = 0.254). The proportion of patients independent at 3 months was 63.2% in EVT and 72.1% in IVT (OR = 0.67, 95% CI = 0.32–1.37, p  = 0.272). Symptomatic intracranial hemorrhages were overall rare and present only in the IVT group (IVT = 5.9% vs EVT = 0%). Mortality at 3 months was also similar between the two groups (IVT = 0% vs EVT = 1.5%). Conclusion: In this multicenter nested analysis, EVT and IVT in patients with acute ischemic stroke due to IPCAO were associated with similar overall good functional outcome and safety. Randomized studies are warranted.